2013
DOI: 10.4103/2230-8210.111637
|View full text |Cite
|
Sign up to set email alerts
|

Complicated urinary tract infections associated with diabetes mellitus: Pathogenesis, diagnosis and management

Abstract: Diabetes mellitus has a number of long-term effects on the genitourinary system. These effects predispose to bacterial urinary tract infections (UTIs) in the patient with diabetes mellitus. Complicated UTIs are also common and potentially life-threatening conditions. They include emphysematous pyelonephritis, emphysematous pyelitis/cystitis, xanthogranulomatous pyelonephritis, renal/perirenal abscess, and renal papillary necrosis. Improved outcomes of these entities may be achieved by early diagnosis, knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 20 publications
(33 reference statements)
1
17
0
Order By: Relevance
“…Consistent with previous studies, lithiasis (48.0%) and diabetes mellitus (33.7%) remained the pre dominant risk factors in the present study [3,8,9,12,16,22] . Diabetes mellitus accounts for 33.3%62.5% of all PNAs [2,7,23] 43.5%47% of RAs [7,16,17] and 28%50%…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with previous studies, lithiasis (48.0%) and diabetes mellitus (33.7%) remained the pre dominant risk factors in the present study [3,8,9,12,16,22] . Diabetes mellitus accounts for 33.3%62.5% of all PNAs [2,7,23] 43.5%47% of RAs [7,16,17] and 28%50%…”
Section: Discussionsupporting
confidence: 81%
“…A similar result was found in the present study. A slight predominance in Table 5 The antibiotic resistance rate of causative pathogens isolated pain, flank mass, signs of sepsis, weight loss, fistula formation and urinary tract complaints [2,4,15,22] . However, patients with RA were more likely subjected to lethargy in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Siderophores have been observed to have higher expression in patients with acute pyelonephritis (Kashani & Eliott, 2013;Vandevelde & Stepanovic, 2014). IroA and IroN are receptors identified for iron uptake, and IroN is an important siderophore receptor in virulence formation of urinary tract infections (UTI) (Kamoun et al, 2013;Saleem & Shah, 2017). A recent study showed that Ent-Cipro, a synthetic siderophore-antibiotic conjugate based on the native Ent (enterobactin, a kind of siderophore) platform affords targeted antibacterial activity against Escherichia coli strains that express the pathogen-associated IroA gene cluster (Neumann et al, 2018).…”
Section: Innovative Applications Of Siderophores In Deciphering Tmentioning
confidence: 99%
“…Most of times it is a urinary infection outcome attended with delay. Diabetes and urinary tract obstructions are risk factors [2]. The bacteria that are more commonly identified are Escherichia coli and Klebsiella pneumoniae.…”
Section: Introductionmentioning
confidence: 99%